The implications of climate-related mobility for human security in Bangladesh’s Ganges Delta: A scoping review - Ma, Suza; Meddings, George; Savelli, Adam (Alliance of Bioversity International and CIAT and ILRI, 2022)
The study—part of the CGIAR Initiative: Securing the Food Systems of Asian Mega-Deltas (AMD) for Climate and Livelihood Resilience —explores the linkages between climate-related mobility and human security in Bangladesh’s Ganges Delta region. By exploring the available evidence through a systematic literature review, the results of previous literature are mapped an analyzed. We then identify evidence gaps and opportunities for future research on climate-related mobility and human security in Bangladesh.